185 Camrelizumab monotherapy or combination therapy in patients with recurrent or metastatic cervical and endometrial carcinoma:a retrospective study. (10th December 2020) - Liu, Hong; Niu, Shuhuai; Fang, Zhaohui; Chen, Xi; Zhang, Qianying
Abstract : Background: Patients with recurrent or metastatic cervical and endometrial carcinoma have poor prognosis and few treatment options. Blocking the interaction between PD-1 and its ligands is a promising treatment strategy. Camrelizumab is a humanised anti-programmed death-1 (anti PD-1) antibody. This study aimed to assess the anti-tumour activity and safety of camrelizumab in patients with recurrent or metastatic cervical and endometrial carcinoma. Methods: We performed a retrospective analysis for recurrent or metastatic cervical and endometrial carcinoma patients. Eligible patients were aged 28–73 years with an Eastern Cooperative Oncology Group performance status of 0 or 2. Patients received camrelizumab alone(200 mg iv d1 q2w)or in combination with chemoradiotherapy/chemotherapy. The primary endpoint was objective response (ORR). The secondary endpoints included disease control rate (DCR), median progression-free survival (mPFS) and safety. Results: A total of 21 patients were enrolled between September 20, 2019, and July 8, 2020. 18 patients were evaluated for efficacy and 21 patients were available for safety analysis. For 18 evaluated patients, the ORR and DCR was 50% (9/18) and 83.3% (15/18), respectively. In addition, 4 patients received camrelizumab monotherapy with the ORR of 0% (0/4) and DCR of 25% (1/4), and 14 patients received camrelizumab combination therapy with the ORR of 64.3% (9/14) and DCR of 100% (14/14). 16 of 21 patients were still receiving the treatment, the median PFS was not yet achieved. Exploratory analysis showed that patients with reactive cutaneous capillary endothelial proliferation (RCCEP) had the higher objective response rate than those without RCCEP (57.1% vs 45.5%). Treatment-related adverse events occurred in 47.6% (10/21) of patients, and the most common adverse events were RCCEP (33.3%), rash (14.3%), dry skin (9.5%). Treatment-related grade 3 adverse events occurred in 4.8% (1/21) of patients. Conclusions: Camrelizumab showed antitumour activity in recurrent or metastatic cervical and endometrial carcinoma with manageable toxicities. Camrelizumab combination therapy had better efficacy compared with monotherapy. RCCEP occurrence was positively associated with outcomes of camrelizumab. Further studies are needed to verify this data.